Δ15N values of atmospheric N species simultaneously collected using sector-based samplers distant from sources – Isotopic inheritance and fractionation. (August 2017) - Savard, Martine M.; Cole, Amanda; Smirnoff, Anna; Vet, Robert
Abstract: The nitrogen isotope ratios (δ 15 N) of atmospheric N species are commonly suggested as indicators of N emission sources. Therefore, numerous research studies have developed analytical methodologies and characterized primary (gases) and secondary emission products (mostly precipitation and aerosols) from various emitters. These previous studies have generally collected either reduced or oxidized N forms, and sampled them separately prior to determining their δ 15 N values. Distinctive isotopic signals have been reported for emissions from various sources, and seasonality of the δ 15 N values has been frequently attributed to shifts in relative contributions from sources with different isotopic signals. However, theoretical concepts suggest that temperature effects on isotopic fractionation may also affect the δ 15 N values of atmospheric reaction products. Here we use a sector-based multi-stage filter system to simultaneously collect seven reduced and oxidized N species downwind from five different source types in Alberta, Canada. We report δ 15 N values obtained with a state-of-the-art gold-furnace pre-concentrator online with an isotope ratio mass spectrometer (IRMS) to provide representative results even for oxidized-N forms. We find that equilibrium isotope effects and their temperature dependence play significant roles in determining the δ 15 N values of the secondary emission products. In the end, seasonal δ 15 N changes here are mainly caused by temperature effects on fractionation, and the δ 15 N values of only two N species from one source type can be retained as potential fingerprints of emissions. Highlights: Seven simultaneously collected air N species yield reproducible δ 15 N analyses. Equilibrium effects significantly influence δ 15 N values of secondary emissions. Seasonal δ 15 N changes are mainly caused by temperature effects on fractionation. New empirical relation describes NH4 + -NH3 fractionation as a function of T. Fractionation in reaction needs to be considered when assessing δ 15 N as fingerprint.